Amorphous Zr(OH)4 to t-ZrO2 transformed isothermally (Superficies y Vacío, 2018)
With the aim to study the transformation from the commercially amorphous Zr(OH)4 to the t-ZrO2, phase, the starting material was isothermally treated in a calorimeter at 350, 365, 370, 375 and 380 o C. The TGA coupled to the DSC technique was used to determine with high precision both the temperature and time necessary to achieve the amorphous Zr(OH)4 to  t-ZrO2 transformation. The mass loss and heat flow, as a function of time, were monitored to study the dehydroxylation of Zr(OH)4 and the crystallization processes, respectively. Raman spectroscopy was used to obtain evidence of the t-ZrO2 formation. The DSC results show an exothermic peak (typical of amorphous-crystalline transitions) related to the formation of t-ZrO2. Our results indicate that the time necessary to obtain the t-ZrO2 phase shortens when temperature increases.